Neurothekeoma palpebrae in association with multiple superficial angiomyxomas : Tegumental Angiomyxoma-Neurothekeoma syndrome (TAN syndrome) - Tan , A.K; Ku, C.Y; Annuar, F.H (Licensee PAGEPress, Italy, 2011)
We report a case of 10-year-old Indian girl with history of multiple superficial angiomyxoma, presented with three months history of painless right upper lid swelling. There were no visual dysfunctions. Previously, the patient had multiple superficial angiomyxoma (left pinna, left upper cheek, left upper limb, chest, right axilla, hard palate) and epidermal cyst (chin). The histopathological specimens were negative to S-100 protein antibody. Systemic review and family history was unremarkable. Excision biopsy and upper lid reconstruction were performed. Intraoperatively the tumor was multilobulated, firm, well encapsulated and did not invade the underlying tarsal plate. Histopathological features of the upperlid tumor were consistent with nerves sheath myxoma (neurothekeoma). To the best of the authors’ knowledge, this is the first reported case of neurothekeoma in association with multiple superficial angiomyxoma.